Analisis Faktor Penentu Kinerja Staff Pengajar Dalam Pelayanan Bimbingan Skripsi Di Fakultas Ekonomi Universitas Kadiri - Eni Prastiti; Nunung Susilaningsih (Universitas Kadiri, 2020)
The purpose of this study is to determine what factors influence staff performance in providing thesis guidance services at the Faculty of Economics, Kadiri University. Sampling used a saturated sample of 24 respondents from teaching staff at the Kadiri University economics faculty. Techniques data by close questionnaires. Factor analysis test uses the KMO test (Kaiser-Meyer-Olkin Measure of Sampling Adequacy). The results showed that there were determinants of the performance of teaching staff in the thesis guidance service on the ability of students to conduct research by 93.7%, in motivating students to be mutually supportive, encouraging enthusiasm and a sense of responsibility towards research by 97.5%, in time management both on the guidance and achievements of students by 88.7%, and the last in the training and development of teacher saff in the work environment and supporting facilities by 94.2%. Tujuan penelitian ini adalah mengetahui faktor – faktor apa yang mempengaruhi kinerja staff dalam memberikan pelayanan bimbingan skripsi di Fakultas Ekonomi Universitas Kadiri. Pengambilan sampel menggunakan sampel jenuh sebanyak 24 responden dari staff pengajar pada fakultas ekonomi Universitas Kadiri. Teknik pengumpulan data dengan cara mengisi kuisioner tertutup. Uji analisis faktor menggunakan uji KMO (Kaiser – Meyer – Olkin Measure Of Sampling Adequacy). Hasil penelitian menunjukkan adanya faktor penentu kinerja staff pengajar daam pelayanan bimbingan skripsi terhadap kemampuan mahasiswa dalam melakukan penelitian sebesar 93,7%, dalam memotivasi mahasiswa bersikap saling mendukung, dorongan semangat dan rasa tanggung jawab terhadap penelitian sebesar 97,5%, dalam manajemen waktu yang baik pada bimbingan dan capaian mahasiswa sebesar 88,7%, dan yang terakhir dalam pelatihan dan pengembangan saff pengajar pada lingkungan kerja dan fasilitas yang mendukung sebesar 94,2%